Використання інформаційних технологій для навчання початкового курсу математики - Остапйовська, Ірина; Свистун, Надія; Теслюк, Софія; Ostapiovska, I.; Svystun, N.; Tesliuk, S. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлюються теоретичні аспекти використання інформаційних технологій у початковій школі, зокрема на уроках математики. Розглянуто можливості використання інформаційних технологій у навчально-виховному процесі, для створення умов активізації пізнавальної і творчої діяльності учнів та окреслено позитивні наслідки від їх застосування у педагогічній діяльності. Досліджено та охарактеризовано оптимальні умови для використання ІТ (при цьому увагу було зосереджено на можливостях уроків математики у молодших класах). Коротко висвітлено окремі методичні прийоми застосування ІТ на уроках математики, наведено їх приклади. Окреслено перспективи подальших досліджень. The theoretical aspects of the use of information technologies in primary school, in particular in the lessons of mathematics are revealed in the article. The possibilities of using information technologies in the teaching and educational process for creating conditions for activating the cognitive and creative activity of pupil are examined, and the positive consequences from their application in pedagogical activity are described. Attention is focused on the requirements for the selection and development of pedagogical software (PS). The optimal conditions for the use of IT were studied and characterized (attention was focused on the possibilities of mathematics lessons in junior classes). Brief descriptions of individual methods of applying IT in mathematics lessons are presented, examples of exercises are given, which are conducted mainly in the form of games with multimedia accompaniment. Prospects for further research have been determined.
The use of information technologies for the teaching the initial course of mathematics
Keywords: інформаційні технології; мультимедіа; інформатизація навчання; методика математики; початкова школа; information technologies; multimedia; informatization of education; methodology of mathematics; primary school